Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1136/bmjgh-2020-002637
|View full text |Cite
|
Sign up to set email alerts
|

Undernutrition, polygynous context and family structure: a multilevel analysis of cross-sectional surveys of 350 000 mother–child pairs from 32 countries

Abstract: BackgroundContextual factors, especially where people live, has been linked to various health outcomes, therefore, there is an increasing focus on its implication for policies and implementation of health interventions. Polygyny is a widespread practice in sub-Saharan Africa that also reflects socioeconomic and sociocultural features. This study investigated the association between polygynous context and risk of undernutrition.MethodsRecent Demographic and Health Surveys involving 350 000 mother–child pairs fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
(32 reference statements)
0
7
0
Order By: Relevance
“…This variable has been defined in the DHS as the number of other wives that the partner of currently married women (women who are either legally or formally married or who are living in a consensual union) has. Reference to the use of this variable has been published elsewhere ( Anjorin et al, 2020 ; Smith-Greenaway & Trinitapoli, 2014 ). However, in this study, only currently married women were considered in order to understand the link between current marital structure and IPV.…”
Section: Methodsmentioning
confidence: 99%
“…This variable has been defined in the DHS as the number of other wives that the partner of currently married women (women who are either legally or formally married or who are living in a consensual union) has. Reference to the use of this variable has been published elsewhere ( Anjorin et al, 2020 ; Smith-Greenaway & Trinitapoli, 2014 ). However, in this study, only currently married women were considered in order to understand the link between current marital structure and IPV.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, polygamy has been shown by Stephen et al in Nigeria [ 31 ] and Lowe et al [ 32 ] in The Gambia to have a negative impact on maternal healthcare utilization. Dilution and scarcity of resources in polygamous families are common mechanisms that are used to explain the decreased likelihood of health facility utilization among women in polygamous relationships [ 12 , 31 , 33 ]. This has been debated against in some literature with some reporting that some polygamous men tend to be wealthy [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given that our findings suggest that there is a positive association between media access and water, sanitation, and hygiene practice, it is possible that mass media could be used as the primary means of health intervention and health education. Published literature has discussed how mass media can be used to promote health knowledge and behaviors [ 46 ]—radios were reportedly the most frequently used channel, followed by television [ 24 , 47 ]. This is consistent with our results, which indicated that radio usage has the highest usage.…”
Section: Discussionmentioning
confidence: 99%